TI-PBFT: Improved Practical Byzantian Fault Tolerance Consensus Mechanism Based on ID-Trust Algorithm - Hussien Faleh, Sajad; Jasim Kadhim, Dheyaa (Iraqi Journal for Electrical and Electronic Engineering, 2026)
Blockchain innovation is gaining attention in fields like monetary exchange, edge computing, medical care, and datasecurity.Consortium chains, using lightweight consensus algorithms like PBFT, offer alternatives to proof-basedmechanisms while maintaining decentralization, security, and scalability. However, it also has some limitations andchallenges that need to be addressed to improve its performance and scalability. PBFT is a classical algorithm withhigh complexity due to three-stage broadcasting and arbitrary selection of master nodes. Its communication efficiencyis low, and scalability issues arise when nodes are large, causing significant delays and performance degradation inunstable networks. Furthermore, the requirement for every node to bundle, check, and broadcast the exchange list inthe pre-prepared, prepared and commit stages diminishes the efficiency of consensus and performance between nodesand comes down on network correspondence. The research proposes a new methodology for the consensus algorithm,focusing on high-trust nodes to protect the network from malicious actors and reducing computational overhead andlatency by eliminating Byzantian nodes and grouping the remaining nodes into groups, each of which has a mainnode selected based on a higher trust score. According to the results, the suggested methodology leads to significantimprovements in communication complexity and Byzantine fault tolerance compared to standard PBFT networks andprevious works. This indicates a substantial enhancement in network efficiency and scalability, offering promisingprospects for blockchain applications in various fields.